2012
DOI: 10.1016/j.jacc.2012.06.053
|View full text |Cite
|
Sign up to set email alerts
|

The Entirely Subcutaneous Implantable Cardioverter-Defibrillator

Abstract: This study demonstrates that the S-ICD is effective in terminating ventricular arrhythmias. There is, however, a considerable percentage of ICD related adverse events, which decreases as the therapy evolves and experience increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(144 citation statements)
references
References 23 publications
6
134
1
3
Order By: Relevance
“…Our results demonstrate that the S‐ICD is safe and effective in terminating both induced and spontaneous VF and corroborate results reported by other researchers and larger groups of patients 3, 4. Our population was generally younger with a more‐preserved ejection fraction than those previously reported in prospective ICD trials, also commonly presenting with a rapid unstable VT/VF, rather than monomorphic VT. We included patients with a primary as well as secondary ICD indication.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results demonstrate that the S‐ICD is safe and effective in terminating both induced and spontaneous VF and corroborate results reported by other researchers and larger groups of patients 3, 4. Our population was generally younger with a more‐preserved ejection fraction than those previously reported in prospective ICD trials, also commonly presenting with a rapid unstable VT/VF, rather than monomorphic VT. We included patients with a primary as well as secondary ICD indication.…”
Section: Discussionsupporting
confidence: 90%
“…One study has demonstrated the association between operator experience and the risk of inadequate therapy 4. Compared with our results, we can confirm that, in our cohort, the patient with inappropriate shocks was implanted at the early phase of the S‐ICD and before the introduction of algorithms for prevention of myopotential oversensing, which may also play an important role in the safety of the S‐ICD system.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Still, the subcutaneous ICD shares many of the same hazards as transvenous ICDs, including lead dislodgement (2.5%), skin erosion (1.7%), and infection (5.9%), along with a 13% incidence of inappropriate shocks during follow-up. 40 Although subcutaneous ICDs have been shown to effectively terminate electrically induced VF, the effectiveness of the subcutaneous ICD compared with the transvenous ICD in improving survival from spontaneous VF has yet to be established. 41 External defibrillators and ICDs offer potential lifesaving therapy for malignant tachyarrhythmias.…”
Section: Defibrillator Technologies and Limitationsmentioning
confidence: 99%
“…Current evidence is based on a certain number of regulatory studies [15,22] as well as several post-marketing studies, mostly multicentric [16,19,21,[27][28][29]. Follow-up remains relatively short, the longest being the pooled analysis of the EFFORTLESS and IDE registries with a mean follow-up of less than 2 years [20].…”
Section: Current Evidencementioning
confidence: 99%